2006
DOI: 10.1111/j.1464-5491.2006.02012.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression and anxiety in adults with Type 1 diabetes

Abstract: While there is no significant difference in the mean anxiety or depression in this cohort compared with those reported for a non-diabetic, healthy population, the results suggest that there is an increased prevalence of clinically relevant anxiety in females and of depression in males with Type 1 diabetes when compared with the normative data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 17 publications
5
48
1
3
Order By: Relevance
“…3 Depression is more prevalent among females with diabetes than among males with diabetes 19 and among patients with Type II versus type I diabetes. 20 In the literature, there are no other studies investigating in which the prevalence of depression among married women with diabetes is investigated separately. However, in some studies, women and married people are reported to be at a higher risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…3 Depression is more prevalent among females with diabetes than among males with diabetes 19 and among patients with Type II versus type I diabetes. 20 In the literature, there are no other studies investigating in which the prevalence of depression among married women with diabetes is investigated separately. However, in some studies, women and married people are reported to be at a higher risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety occurs more frequently in patients with diabetes than in a general population [5] and only results of some researches do not confi rm this tendency [6,7]. The increased level of anxiety has been described in 40% of patients [8].…”
Section: Cel I Założeniamentioning
confidence: 99%
“…Nie jest też wykluczone, że związek pomiędzy obawą przed hipoglikemią a lękiem jako cechą jest obustronny. Dobrym przykła-dem może być tu opis przypadku strachu przed hipoglikemią, który doprowadził do ataków paniki z agorafobią [4].U pacjentów z cukrzycą stwierdza się zazwyczaj nieco częstsze niż w populacji ogólnej występowanie zaburzeń lękowych [5] i tylko wyniki niektórych badań nie potwierdzają tej prawidłowości [6,7]. Podwyższony poziom lęku opisywano aż u 40% pacjentów [8].…”
unclassified
See 1 more Smart Citation
“…[1] The prevalence of depression and anxiety in diabetes is considerably higher than normal population and ranges between 12 and 28%. [2][3][4] Both diabetes and anxiety/depression are independently associated with increased morbidity and mortality. Co-occurrence of these conditions adds to the cost, morbidity, and mortality.…”
Section: Introductionmentioning
confidence: 99%